Exploring the Role of Ayurveda in Prediabetes Management: Insights from Experimental and Clinical Evidence - Neelakanta J Sajjanar; Gajanana Hegde (RGUHS Journal of AYUSH Sciences)
Prediabetes a condition marked by elevated blood glucose levels that do not yet meet the threshold for Type 2 diabetes is becoming increasingly prevalent worldwide and is projected to affect an estimated 470 million people by 2030. Without timely intervention many individuals with prediabetes may progress to diabetes increasing the risk of severe complications. This narrative review examines the role of Ayurveda in prediabetes by analyzing eight peer-reviewed studies selected through an extensive literature search across databases such as ScienceDirect PubMed and EBSCO with a focus on recent English-language publications up to March 2024. The chosen studies encompass a variety of Ayurvedic approaches including diagnostics purification therapies polyherbal formulations immune modulation and dietary considerations in the care of prediabetes. Notable findings include Ayurvedic diagnostic indicators that may signal early-stage diabetes and the use of Vamana Karma combined with Darvyadi Kwatha which demonstrated improved glycaemic control and overall well-being. The Nisha-Amalaki formulation enhanced insulin sensitivity and glycaemic balance and the immune-modulating formulation Kal-1 showed potential for managing blood glucose and inflammation in a preclinical study. Additionally a dietary preclinical survey revealed that prolonged fermentation of curd may have a negative impact on metabolic health in prediabetic conditions. Collectively these studies underline Ayurvedas potential in delaying or preventing the onset of Type 2 diabetes through holistic and preventive strategies providing a complementary approach to modern healthcare practices.